Discussion on the common threshold of several exponential distributions with different rates. Issue 12 (18th June 2017) - Lin, S. H.; Wang, R. S.
ABSTRACT: The integration of results of independent studies in order to make inferences about a common threshold is an important problem with many practical applications. In this article, we apply the generalized variable method to make inferences on the common threshold of several exponential distributions when the scale (or rate) parameters are unknown and unequal. The merits of the proposed method are computed numerically and compared with other existing methods. Numerical results of both simulation studies and real data analyses show that the proposed method is applicable and its performance is better than other methods even when sample sizes are small.